Anti-hyperglycemic effect of Phaleria macrocarpa fruit aqueous extract in type I diabetic mellitus-induced rats - Dollah, Mohamad Aziz; Mohamad Kamal, Siti Raudzah (Sarawak Biodiversity Centre, 2008)
Phaleria macrocarpa is used traditionally to treat various diseases. Its fruits are claimed to give antihyperglycemic effect to those people suffering from diabetes mellitus. The scientific information on the hypoglycemic properties however is not conclusive. For this reason, an experiment was conducted to evaluate the anti-hyperglycemic properties of P. macrocarpa fruit aqueous extract in diabetic-induced rats. A two by three randomized experimental design was used with two periods of supplementation (14 and 28 days) and three concentration levels (0, 90 and 180 mg / kg) of P. macrocarpa fruit aqueous extract as the factors. Thirty six diabetic-induced Sprague Drawly female rats were divided into six groups and each group was allocated to one of the treatment. Rats in each group were administered with 0.2 ml of P. macrocarpa fruit aqueous extract orally once a day. The blood glucose level was measured twice a week while the bodyweight of the animals were monitored once a week. The means of body weight of diabetic-induced rats for 28 days of P. macrocarpa supplementation at 0, 90 and 180 mg/kg were 202.67±32.77, 186.69±32.41 and 225.53±20.65 g respectively. The means of body weight of diabetic-induced rats for 14 days of PM supplementation were 188.47±44.21, 192.36±30.29 and 218.89±25.37 g for 0, 90 and 180 mg / kg of P. macrocarpa supplementation respectively. The means of blood glucose level of diabetic-induced rats for 28 days of P. macrocarpa supplementation at 0, 90 and 180 mg/kg were 19.26±4.47, 12.94±7.58 and 10.23±4.07 mmol/L respectively. The means of blood glucose level of diabetic-induced rats for 14 days of PM supplementation at 0, 90 and 180 mg/kg were 20.73±6.48, 12.80±6.21 and 10.89±5.79 mmol/L respectively. The results showed that P. macrocarpa has anti hyperglycemic activity by reducing blood glucose level in diabetic-induced rats and the effect was found to be dose dependent. Consumption of P. macrocarpa fruit aqueous extract for a minimum of 17 days at the dose of at least 90 mg/kg was found to be sufficiently reduced the blood glucose level to the normal level in diabetic-induced rats.